Analisis Nilai-Nilai Spiritual dalam Tradisi Posuo Masyarakat Buton: Analysis of Spiritual Values in the Posuo Tradition of Butonese People - Risman, Kadar; Faridi, Faridi; Tobroni, Tobroni (Anterior Jurnal, 2024)
This research examines spiritual values in the posuo tradition of the Butonese people. The posuo tradition is a traditional ceremony for girls that marks the transition from adolescence to adulthood, carried out once in a lifetime. The approach and type of research used is a qualitative approach with library research. Data was obtained through relevant literature, including books, journals, articles, and research reports. The findings show that the posuo tradition contains four main spiritual values based on Notonegoro's theory, namely the values of beauty, truth, goodness, and religiosity. The value of beauty can be seen in traditional clothing and ceremonies, The truth value of implementing customs is by the teachings passed down from generation to generation and still refers to a combination of Islamic teachings and established customary rules., the value of goodness from ethical and moral education, and the value of religiosity from spiritual practices during ceremonies. This tradition not only functions as a means of self-cleaning but also as a medium for education and character formation which is important for Butonese women in living their adult lives.